OCCUPATIONAL INJURIES AND ILLNESSES IN RUBBER FACTORY: PROFILE, POTENTIAL HAZARDS AND POSSIBLE PREVENTION - Irfani, Tri Hari (Public Health of Indonesia, 2015)
Rubber is one of the important commodities in the world. Globally, workers are facing so many problems of hazards that produce by rubber process. In Indonesia, there are several data of occupational problems such as respiratory diseases, muscle and skeletal diseases, gastrointestinal diseases, diseases of the teeth and oral cavity, skin diseases and skin tissue. In Iranian rubber factory, Iran, workers had suffered from some kind of musculoskeletal symptoms. Stomach and liver cancers in workers are having in Shanghai tire factory. In addition, Germany has cancer problem of their workers who work in rubber factory. Most of the rubber process in the factory can cause some hazards of the workers. In unloading area and area that operator is taking the dirt manually, workers are facing ergonomic problems. The possible control is reduce weight of load, team lift the object with two or more workers and Use mechanical assist. Machine safeguarding is essential for protecting from Cutting process that can make workers amputation organs such as hands, and fingers. In bale process, the workers need to cut raw rubber into bale in bale cutting. Furthermore, workers are facing with amputation problem. To manage that, It must be designed as a standard which has interlocking guards to prevent access to the cutting area. When wrapped using plastic, workers use a heated iron and sticked in plastic so that it blends neatly. The risks are fingers can cut accidently and then the workers also get contamination from polyvinyl chloride (PVC). The possible preventions are use an automatic plastic wrapping machine with palletized product sitting on a turntable and respirator. Another problem is contact dermatitis that has been reported frequently among rubber workers. The prevention for that problem is using Gloves. The aim of researcher is to provide the profile of occupational injuries and illnesses, potential hazards in rubber factory to prevent the workers.